The Development of Village Fund into an Integrated Community Financial Institution - Pakdeewut, Jureewan (Humanities, Arts and Social Sciences Studies, 2013)
Following to the setting up of the 1 million baht village fund scheme in 2001, the Thai government has contributed 74,865 million baht to each village in total (National Village and Urban Community Fund Office, 2010). This money becomes the working capital and accessible financial source for people in the rural villages. The government plans to upgrade the village fund to become the community financial institution serving as the main financial source for the community. The problems are that village fund administrators and the community members are not ready for the operation and there is no clear approach for setting up community financial institution. This research aimed to study the development of the village fund into community financial institution in Roi Et and to propose an appropriate approach to establish an integrated community financial institution in order to become choices for village fund to upgrade into community fund in the future. This research was of qualitative and quantitative one. In qualitative study, the semi-structure in-depth interview was administered to the target groups which were model community financial institution administrators and relevant government workers. In quantitative investigation, the questionnaire was used to collect information from committees of the village funds and members of the village funds in Roi Et province. The data were collected from committees and members of village fund in Roi Et province totally 372 funds. The content analysis was used to analyze qualitative data and descriptive statistics were used to analyze the quantitative data. From the data analysis, the researcher proposed the integrated community financial institution as an optional form of community financial institution, mandated to accumulate fund for a better administration. The principle was to provide equal opportunity and fair allocation to people in the community getting in access to the funds. This can be a choice of financial institution administration with its simple and flexible steps for different community background. In this research, there was also an investigation of effective financial institution. It was found that having efficient and honest committee was very important. Other important features were the cooperation and royalty of members, the sufficient funds in the community as well as the readiness of facilities and the participation of people in the community.